Feasibility and Efficacy of Prolonged Exposure for PTSD among Individuals with a Psychotic Spectrum Disorder - Grubaugh, Anouk L.; Veronee, Kimberly; Ellis, Charles; Brown, Wilson; Knapp, Rebecca G. (Frontiers in Psychology, 2017)
Objective: Few empirical studies have examined the feasibility of trauma-focused treatment among individuals with schizophrenia. This lack of research is important given the substantial overlap of trauma exposure and subsequent PTSD with psychotic spectrum disorders, and the potential for PTSD to complicate the course and prognosis of schizophrenia and other variants of severe mental illness. Method: As part of a larger study, 14 veterans with a psychotic spectrum disorder were enrolled to receive prolonged exposure (PE) for PTSD within a single arm open trial study design. Patient reactions and responses to PE were examined using feasibility indices such as attrition, survey reactions, and treatment expectancy; pre and post-changes in PTSD severity and diagnostic status; and thematic interviews conducted post-intervention. Results: Quantitative and qualitative data indicate that implementation of PE is feasible, subjectively well-tolerated, and may result in clinically significant reductions in PTSD symptoms in patients with psychotic spectrum disorders. Conclusion: Consistent with treatment outcome data in clinical populations with a broader range of severe mental illnesses, the current results support the use of PTSD exposure-based interventions, such as PE, for individuals with psychotic spectrum disorders.